Atomic-scale passivation strategy for stabilizing tricolor perovskite quantum dots with enhanced photoluminescence - Yilei Zhang; Di Wen; Min Wang; Tianwei Zhang; Kun Cao; Rong Chen (Journal of Information Display)
Perovskite quantum dots (QDs) are promising light-emitting materials for next-generation displays. Nevertheless, their practical applications are hindered by poor stability. In this study, we present a mild atomic layer deposition (ALD) method using dimethylaluminum isopropoxide (DMAI) precursor at a lower temperature (50 °C) to enable simultaneous stabilization of the RGB QDs while enhancing their photoluminescence (PL) intensity. The DMAI precursors react with the –COOH groups of oleic acid, passivating surface defects by forming Al–O bonds between the ligands and perovskite QDs, thereby improving optical performance. This is followed by the formation of a nanoscale AlOx thin film coating that protects the octahedral structure of the ODs. The passivated perovskite RGB QDs exhibit significantly enhanced PL intensity and prolonged fluorescence lifetime, retaining over 80% of their PL after exposure to water, intense light, and temperatures up to 150 °C. Furthermore, when used in tri-color micro-LEDs, the modified RGB perovskite QDs demonstrates 8 times longer operational stability compared to the original QDs. White LEDs have been also fabricated, exhibiting narrow spectra and stable PL intensity. These results highlight the potential of the mild ALD method with DMAI precursor in enhancing the stability and efficiency of optoelectronic devices under manufacturing and operating conditions.